Post-Quantum Cryptography Resilience in Telehealth Using Quantum Key Distribution - Roosan, Don; Khan, Rubayat; Nirzhor, Saif; Hai, Fahmida (Blockchain in Healthcare Today, 2025)
Context The study proposes and evaluates a novel cybersecurity architecture for telehealth, resilient against future quantum computing cyber threats. By integrating Post-Quantum Cryptography (PQC) with Quantum Key Distribution (QKD) and privacy-preserving mechanisms, data confidentiality and immutability for patient records in a post-quantum era are ensured. Methods A multi-layered design approach was adopted. PQC algorithms (e.g., CRYSTALS-Dilithium) were integrated at the blockchain consensus layer to resist quantum attacks. A Directed Acyclic Graph (DAG)-based ledger managed high transaction throughput and latency constraints typical of telehealth. A QKD-enhanced key management protocol leveraged quantum channels for secure exchanges. Zero-knowledge proofs (ZKPs) and secure multiparty computation (MPC) verified transactions without exposing sensitive patient data. A granular access control model used attribute-based encryption (ABE) and smart contracts to govern which participants could view or modify encrypted medical records. Results The prototype was developed within a simulated telehealth network comprising hospitals, clinics, and patient devices. PQC signatures at the consensus layer provided effective resistance to both classical and anticipated quantum attacks. QKD facilitated secure key distribution, while ZKPs and MPC enabled validation of healthcare transactions without compromising patient privacy. Despite increased computational overhead, the DAG approach efficiently handled parallel transactions, indicating improved scalability compared to traditional linear blockchains. Conclusion A QKD-enhanced, PQC-driven framework successfully addresses critical security and privacy requirements, safeguarding medical data from emerging quantum threats. Although overhead and infrastructural costs are significant, sustained cryptographic resilience and robust patient confidentiality underscore its suitability for next-generation healthcare systems. Future studies should explore additional optimizations, homomorphic encryption, and larger-scale pilots under regulatory standards.